MENINGKATKAN TEKNIK EGOS SABIT MENGUNAKAN METODE BAGIAN PADA PPS SATRIA MUDA INDONESIA - Abdurrauf Abdul Karim (Journal of Physical Education and Sport Science, 2020)
This study aims to improve the sickle egos technique with a speed approach at the Indonesian Satria Muda PPS Training Unit at SMP Barunawati II Tanjung Priok, North Jakarta. This research was conducted in April at the Barunawati II Middle School training unit. The subjects who were the subjects of this study were students or athletes of the PPS Satria Muda Indonesia martial arts training unit at SMP Barunawati II Tanjung Priok, North Jakarta.The method used in this research is descriptive research method with Classroom Action Research, namely by giving special treatment to athletes to improve the sickle egos technique with a speed approach at the Pencak Silat College. The indicators measured in this study are: preparation movement, implementation movement, follow-up movement. Based on the results of the research, it can be concluded that: with action research and using the method of partially training, it can improve the sickle egos technique with a speed approach at PPS Satria Muda Indonesia Training Unit SMP Barunawati II Tanjung Priok North Jakarta. With two cycles of action research. From the success rate of students on the initial test amounted to 3 or 15%, then after being trained by the part-by-part method in cycle I the students succeeded in amounting to 14 or 70%, and because they did not reach the target, it was continued until cycle II where in cycle II the success of students achieved 18 people or 90% complete